Prevalence And Associated Factors of Hypertension Among Occupational Bus Drivers in Nagpur City, Central India- A Cross Sectional Study - Borle, Amod L; Jadhao, Ashok (National Journal of Community Medicine, 2015)
Introduction: This study was done to study the prevalence of hy- pertension and factors related to it among bus drivers working in four bus depots of Maharashtra State Road Transport Corporation (M.S.R.T.C.), of Nagpur City in Central India. Method: Present cross-sectional study was carried out among bus drivers of MSRTC bus depots of Nagpur city. The data was col- lected with the help of interview method using structured ques- tionnaire. History taking included personal details, occupational history, socio-demographic details, family history, presenting com- plaints, past history, duration of driving (hrs.), and daily average driving (km). Results: Prevalence of hypertension was found to be 34.8%. Hy- pertension was significantly associated with various socio-demo- graphic characteristics like age, socio-economic status, education, family h/o hypertension, BMI and certain occupational character- istics like duration of service, daily average driving, duration of driving per week. Conclusion: Prevalence of hypertension was high among bus driv- ers. Study emphasize the need for the periodic screening and reg- ular follow up of drivers for diagnosis and maintaining the com- pliance with the treatment. Also there is need for targeted educa- tional interventions and lifestyle modifications among bus drivers.